Aquifer Vulnerability Assessment Based on Sequence Stratigraphic and 39Ar Transport Modeling. Issue 2 (27th May 2015) - Sonnenborg, Torben O.; Scharling, Peter B.; Hinsby, Klaus; Rasmussen, Erik S.; Engesgaard, Peter
Abstract: A large‐scale groundwater flow and transport model is developed for a deep‐seated (100 to 300 m below ground surface) sedimentary aquifer system. The model is based on a three‐dimensional (3D) hydrostratigraphic model, building on a sequence stratigraphic approach. The flow model is calibrated against observations of hydraulic head and stream discharge while the credibility of the transport model is evaluated against measurements of 39 Ar from deep wells using alternative parameterizations of dispersivity and effective porosity. The directly simulated 3D mean age distributions and vertical fluxes are used to visualize the two‐dimensional (2D)/3D age and flux distribution along transects and at the top plane of individual aquifers. The simulation results are used to assess the vulnerability of the aquifer system that generally has been assumed to be protected by thick overlaying clayey units and therefore proposed as future reservoirs for drinking water supply. The results indicate that on a regional scale these deep‐seated aquifers are not as protected from modern surface water contamination as expected because significant leakage to the deeper aquifers occurs. The complex distribution of local and intermediate groundwater flow systems controlled by the distribution of the river network as well as the topographical variation (Tóth 1963) provides the possibility for modern water to be found in even the deepest aquifers.